A BRIEF DISCUSSION ON MISDEMEANOR SANCTIONS WITH SPECIAL EMPHASIS ON THEIR SIGNIFICANCE IN ENVIRONMENTAL PROTECTION - Samardžić, Stefan; Milić, Ivan D. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
In this paper, the authors deal with specific aspects of misdemeanour sanctions, with special emphasis on misdemeanour sanctions prescribed by the Law on Environmental Protection and certain related decisions of lower legal power. Although misdemeanours are considered the least dangerous offenses, the authors strive to show that sanctions for certain misdemeanours should not be easily ignored, as sometimes they could be even more severe than criminal sanctions. One of the topics discussed in this paper is the forced collection of misdemeanour fines as well as the entry of convicts into the misdemeanour records. Since not only the law can prescribe misdemeanours, rather they could be prescribed by ordinance or even by some decision of local governing bodies, there is a huge number of existing misdemeanours in the area of environmental protection, which is the argument for special attention to the topic of this article. The authors would try to highlight certain inconsistencies in specific local governing bodies’ decisions, as well as their misalignment with the Misdemeanour Law.